Leis de devida diligência empresarial em direitos humanos e proteção do sistema climático: uma análise a partir das duas primeiras decisões da justiça francesa - Janine Rodrigues de Oliveira Trindade (2024)
In the past five decades, the corporate world has experienced progressive expansion. Companies have grown on a global scale and their profits have risen significantly. However, the international human rights law, established since the 1940s, does not reach these economic entities, making it challenging to safeguard human rights and the environment. In today’s times of climate emergency, the accountability gap is concerning as it fails to encourage companies to adopt a trajectory towards achieving global climate goals. In this context, this dissertation seeks to answer the following problem: what legal mechanisms are available for companies to contribute to global climate change policy? One hypothesis is that laws on Human Rights Due Diligence (HRDD) can compel private agents to align their operations with a sustainable business model that considers the need to maintain the balance and stability of the planet. The dissertation aims to analyse the protective potential of HRDD laws for the climate system. This analysis is based on the study of five European HRDD laws, insights from international experts in human rights and corporate affairs, and two French judicial decisions against Total Energies S/A. To fulfil the general objective, the initial section elucidates the ecological crisis in the Anthropocene and the progressive transgression of the Earth’s safe and equitable planetary boundaries, while also delving into the interrelation between human rights and the environment and human rights and climate change. The second section discusses the governance crisis spurred by economic globalization, traces the historical trajectory of the United Nations’ (UN) agenda on business and human rights, elucidates the content of UN Guiding Principles on Business and Human Rights (UNGPs), and explores the contributions and criticisms attributed to the UNGPs, which provide the basis of HRDD laws. The same section also addresses the international framework for combating climate change and, finally, discusses an alternative approach to tacking the climate that doesn’t solely rely on state commitments but on the responsibility of major fossil fuel companies. The third section evaluates five European HRDD laws, specifically those of France, the Netherlands, Switzerland, Germany and Norway. The fourth section theoretically examines the contributions and limitations of HRDD laws and subsequently analyses the first two French court decisions in climate litigation challenging the application of domestic HRDD laws. The main conclusion is that HRDD laws may prove insufficient to protect the climate system if their application is not contextualized with the consensus of climate science and international human rights and the environmental law. The research is qualitative and exploratory. It predominantly utilizes the hypothetical-deductive method. The methodological framework is bibliographic and documentary.